36th International Symposium on Intensive Care and Emergency Medicine. Issue 2 (April 2016) - Bateman, R.; Sharpe, M.; Jagger, J.; Ellis, C.; SolÃ©-ViolÃ¡n, J.; LÃ³pez-RodrÃguez, M.; Herrera-Ramos, E.; RuÃz-HernÃ¡ndez, J.; BorderÃas, L.; Horcajada, J.; GonzÃ¡lez-Quevedo, N.; Rajas, O.; et al.
Table of contents P001 - Sepsis impairs the capillary response within hypoxic capillaries and decreases erythrocyte oxygen-dependent ATP efflux R. M. Bateman, M. D. Sharpe, J. E. Jagger, C. G. Ellis P002 - Lower serum immunoglobulin G2 level does not predispose to severe flu. J. SolÃ©-ViolÃ¡n, M. LÃ³pez-RodrÃguez, E. Herrera-Ramos, J. RuÃz-HernÃ¡ndez, L. BorderÃas, J. Horcajada, N. GonzÃ¡lez-Quevedo, O. Rajas, M. Briones, F. RodrÃguez de Castro, C. RodrÃguez Gallego P003 - Brain protective effects of intravenous immunoglobulin through inhibition of complement activation and apoptosis in a rat model of sepsis F. Esen, G. Orhun, P. Ergin Ozcan, E. Senturk, C. Ugur Yilmaz, N. Orhan, N. Arican, M. Kaya, M. Kucukerden, M. Giris, U. Akcan, S. Bilgic Gazioglu, E. Tuzun P004 - Adenosine a1 receptor dysfunction is associated with leukopenia: A possible mechanism for sepsis-induced leukopenia R. Riff, O. Naamani, A. Douvdevani P005 - Analysis of neutrophil by hyper spectral imaging - A preliminary report R. Takegawa, H. Yoshida, T. Hirose, N. Yamamoto, H. Hagiya, M. Ojima, Y. Akeda, O. Tasaki, K. Tomono, T. Shimazu P006 - Chemiluminescent intensity assessed by eaa predicts the incidence of postoperative infectious complications following gastrointestinal surgery S. Ono, T. Kubo, S. Suda, T. Ueno, T. Ikeda P007 - Serial change of c1 inhibitor in patients with sepsis â€" A prospective observational study T. Hirose, H. Ogura, H. Takahashi, M. Ojima, J. Kang, Y. Nakamura, T. Kojima, T. Shimazu P008 - Comparison of bacteremia and sepsis on sepsis related biomarkers T. Ikeda, S. Suda, Y. Izutani, T. Ueno, S. Ono P009 - The changes of procalcitonin levels in critical patients with abdominal septic shock during blood purification T. Taniguchi, M. O P010 - Validation of a new sensitive point of care device for rapid measurement of procalcitonin C. Dinter, J. Lotz, B. Eilers, C. Wissmann, R. Lott P011 - Infection biomarkers in primary care patients with acute respiratory tract infections â€" Comparison of procalcitonin and C-reactive protein M. M. Meili, P. S. Schuetz P012 - Do we need a lower procalcitonin cut off? H. Hawa, M. Sharshir, M. Aburageila, N. Salahuddin P013 - The predictive role of C-reactive protein and procalcitonin biomarkers in central nervous system infections with extensively drug resistant bacteria V. Chantziara, S. Georgiou, A. Tsimogianni, P. Alexandropoulos, A. Vassi, F. Lagiou, M. Valta, G. Micha, E. Chinou, G. Michaloudis P014 - Changes in endotoxin activity assay and procalcitonin levels after direct hemoperfusion with polymyxin-b immobilized fiber A. Kodaira, T. Ikeda, S. Ono, T. Ueno, S. Suda, Y. Izutani, H. Imaizumi P015 - Diagnostic usefullness of combination biomarkers on ICU admission M. V. De la Torre-Prados, A. Garcia-De la Torre, A. Enguix-Armada, A. Puerto-Morlan, V. Perez-Valero, A. Garcia-Alcantara P016 - Platelet function analysis utilising the PFA-100 does not predict infection, bacteraemia, sepsis or outcome in critically ill patients N. Bolton, J. Dudziak, S. Bonney, A. Tridente, P. Nee P017 - Extracellular histone H3 levels are inversely correlated with antithrombin levels and platelet counts and are associated with mortality in sepsis patients G. Nicolaes, M. Wiewel, M. Schultz, K. Wildhagen, J. Horn, R. Schrijver, T. Van der Poll, C. Reutelingsperger P018 - Il-8: is this a more reliable biomarker for sepsis severity than CRP, Procalcitonin, E-selectin, IL-6 and TNF-[alpha] S. Pillai, G. Davies, G. Mills, R. Aubrey, K. Morris, P. Williams, P. Evans P019 - Relation between adrenomedullin and short-term outcome in ICU patients: Results from the frog ICU study E. G. Gayat, J. Struck, A. Cariou, N. Deye, B. Guidet, S. Jabert, J. Launay, M. Legrand, M. LÃ©one, M. Resche-Rigon, E. Vicaut, A. Vieillard-Baron, A. Mebazaa P020 - Impact of disease severity assessment on performance of heparin-binding protein for the prediction of septic shock R. Arnold, M. Capan, A. Linder, P. Akesson P021 - Kinetics and prognostic value of presepsin (sCD14) in septic patients. A pilot study M. Popescu, D. Tomescu P022 - Comparison of CD64 levels performed by the facs and accellix systems C. L. Sprung, R. Calderon Morales, G. Munteanu, E. Orenbuch-Harroch, P. Levin, H. Kasdan, A. Reiter, T. Volker, Y. Himmel, Y. Cohen, J. Meissonnier P023 - Diagnosing sepsis in 5Â minutes: Nanofluidic technology study with pancreatic-stone protein (PSP/ reg) L. Girard, F. Rebeaud P024 - How nanotechnology-based approaches could contribute to sepsis prevention, diagnosis and treatment I. Herrmann P025 - Il7r transcriptional expression analysis during septic shock B. Delwarde, E. Peronnet, E. Cerrato, F. Venet, A. Lepape, T. RimmelÃ©, G. Monneret, J. Textoris P026 - Disbalance of microbial metabolites of aromatic acids affects the severity in critically ill patients N. Beloborodova, V. Moroz, A. Osipov, A. Bedova, Y. Sarshor, A. Pautova, A. Sergeev, E. Chernevskaya P027 - Copeptin predicts 10-year all-cause mortality in community patients J. Odermatt, R. Bolliger, L. Hersberger, M. Ottiger, M. Christ-Crain, B. Mueller, P. Schuetz P028 - Identification of differential proteomic response in septic patients secondary to community and hospital acquired pneumonia N. K. Sharma, A. K. Tashima, M. K. Brunialti, F. R. Machado, M. Assuncao, O. Rigato, R. Salomao P029 - Monocyte HLA-DR expression in community-acquired bacteremic sepsis - dynamics associated to aetiology and prediction of secondary sepsis S. C. Cajander, G. Rasmussen, E. Tina, B. SÃ¶derquist, J. KÃ¤llman, K. StrÃ¥lin P030 - Soluble B- and T-lymphocyte attenuator: A possible prognostic marker in sepsis A. L. Lange, J. S. SundÃ©n-Cullberg, A. M. Magnuson, O. H. Hultgren P031 - Fractal dimension: A new biomarker for quantifying clot microstructure in patients across the sepsis spectrum G. Davies, S. Pillai, G. Mills, R. Aubrey, K. Morris, P. Williams, P. Evans P032 - Comparison between the new biomarker for coagulation, clot microstructure (Df) with rotational thromboelastometry (ROTEM) in patients across the sepsis spectrum S. Pillai, G. Davies, G. Mills, R. Aubrey, K. Morris, P. Williams, P. Evans P033 - Changes in fibrinolysis across the sepsis spectrum: The use of rotational thromboelastometry (ROTEM) lysis index (LI60) and D-Dimer concentration S. Pillai, G. Davies, G. Mills, R. Aubrey, K. Morris, P. Williams, P. Evans P034 - The intensive care infection score â€" a promising marker for the prediction of infection and its severity. P. Van der Geest, M. Mohseni, J. Linssen, R. De Jonge, S. Duran, J. Groeneveld P035 - Challenges in the clinical diagnosis of sepsis R. Miller III, B. K. Lopansri, L. C. McHugh, A. Seldon, J. P. Burke P036 - Does zero heat flux thermometry more accurately identify sepsis on intensive care? J. Johnston, R. Reece-Anthony, A. Bond, A. Molokhia P037 - Advancing quality (AQ) sepsis programme: Improving early identification & treatment of sepsis in North West England. C. Mcgrath, E. Nsutebu P038 - Prehospital transport of acute septic patients P. Bank Pedersen, D. Pilsgaard Henriksen, S. Mikkelsen, A. Touborg Lassen P039 - Vasodilatory plant extracts gel as an alternative treatment for fever in critically ill patients R. Tincu, C. Cobilinschi, D. Tomescu, Z. Ghiorghiu, R. Macovei P040 - Host response and outcome of hypothermic sepsis M. A. Wiewel, M. B. Harmon, L. A. Van Vught, B. P. Scicluna, A. J. Hoogendijk, J. Horn, A. H. Zwinderman, O. L. Cremer, M. J. Bonten, M. J. Schultz, T. Van der Poll, N. P. Juffermans, W. J. Wiersinga P041 - Septic shock alert over SIRS criteria has an impact on outcome but needs to be revised G. Eren, Y Tekdos, M. Dogan, O. Acicbe, E. Kaya, O. Hergunsel P042 - Association between previous prescription of Î²blockers and mortality rate among septic patients: A retrospective observational study S. Alsolamy, G. Ghamdi, L. Alswaidan, S. Alharbi, F. Alenezi, Y. Arabi P043 - Recognition and treatment of sepsis on labour wardâ€" teaching & information resources can improve knowledge J. Heaton, A. Boyce, L. Nolan, J. Johnston, A. Dukoff-Gordon, A. Dean, A. Molokhia P044 - Culture negative sepsis in the ICU â€" what is unique to this patient population? T. Mann Ben Yehudah P045 - Organ dysfunction in severe sepsis patients identified in administrative data in Germany, 2007-2013 C. Fleischmann, D. Thomas-Rueddel, C. Haas, U. Dennler, K. Reinhart P046 - A comparison of residentsâ€™ knowledge regarding; the Surviving Sepsis Campaign 2012 guideline O. Suntornlohanakul, B. Khwannimit P047 - Effectiveness of a septic shock bundle to improve outcomes in the ICU F. Breckenridge, A. Puxty P048 - Dose of norepinephrine in the first 24Â hours as a parameter evaluating the effectiveness of treatment in patients with severe sepsis and septic shock P. Szturz, P. Folwarzcny, J. Svancara, R. Kula, P. Sevcik P049 - Norepinephrine or vasopressinâ€‰+â€‰norepinephrine in septic shock. A retrospective series of 39 patients L. Caneva, A. Casazza, E. Bellazzi, S. Marra, L. Pagani, M. Vetere, R. Vanzino, D. Ciprandi, R. Preda, R. Boschi, L. Carnevale P050 - Methylene blue effectiveness as contributory treatment in patients with septic shock V. Lopez, M. Aguilar Arzapalo, L. Barradas, A. Escalante, J. Gongora, M. Cetina P051 - Coagulation disorders in patients with severe sepsis and DIC evaluated with thromboelastometry. B Adamik, D Jakubczyk, A KÃ¼bler P052 - Frequency and outcome of early sepsis-associated coagulopathy A. Radford, T. Lee, J. Singer, J. Boyd, D. Fineberg, M. Williams, J. Russell P053 - Assessment of coagulopathy in cancer patients with severe sepsis or septic shock. A case-control pilot study E. Scarlatescu, D. Tomescu, G. Droc, S. Arama P054 - Thromboelastometry in critically ill patients with disseminated intravascular coagulation M. MÃ¼ller, M. Straat, S. S. Zeerleder, N. P. Juffermans P055 - Cessation of a preexisting chronic antiplatelet therapy is associated with increased mortality rates in severe sepsis and septic shock C. F. Fuchs, C. S. Scheer, S. W. Wauschkuhn, M. V. Vollmer, K. M. Meissner, S. K. Kuhn, K. H. Hahnenkamp, S. R. Rehberg, M. G. GrÃ¼ndling P056 - Neutrophil Extracellular Traps (NETs) production under hypoxic condition N. Yamamoto, M. Ojima, S. Hamaguchi, T. Hirose, Y. Akeda, R. Takegawa, O. Tasaki, T. Shimazu, K. Tomono P057 - Impact of ultraviolet air sterilizer in intensive care unit room, and clinical outcomes of patients E. GÃ³mez-SÃ¡nchez, M. Heredia-RodrÃguez, E. Ãlvarez-Fuente, M. Lorenzo-LÃ³pez, E. GÃ³mez-Pesquera, M. AragÃ³n-Camino, P. Liu-Zhu, A. SÃ¡nchez-LÃ³pez, A. HernÃ¡ndez-Lozano, M. T. PelÃ¡ez-JareÃ±o, E. Tamayo P058 - Focus of infection in severe sepsis - comparison of administrative data and prospective cohorts from Germany D. O. Thomas-RÃ¼ddel, C. Fleischmann, C. Haas, U. Dennler, K. Reinhart P059 - â€œZero CLABSIâ€ â€" can we get there? Obstacles on the 4Â year journey and our strategies to overcome them â€" experience from an Indian ICU V. Adora, A. Kar, A. Chakraborty, S. Roy, A. Bandyopadhyay, M. Das P060 - Novel molecular techniques to identify central venous catheter (CVC) associated blood stream infections (BSIs) T. Mann Ben Yehudah, G. Ben Yehudah, M. Salim, N. Kumar, L. Arabi, T. Burger, P. Lephart, E. Toth-martin P061 - Zero clabsiâ€ â€" can we get there? Obstacles on the 4Â year journey and our strategies to overcome them â€" experience from an Indian ICU R. Rao, A. Kar, A. Chakraborty P062 - Prevention of central line-associated bloodstream infections in intensive care units: An international online survey C. Valencia, N. Hammami, S. Blot, J. L. Vincent, M. L. Lambert P063 - 30Â days antimicrobial efficacy of non-leaching central venous catheters J. Brunke, T. Riemann, I. Roschke P064 - Efficacy of noble metal alloy-coated catheter in prevention of bacteriuria R. Tincu, C. Cobilinschi, D. Tomescu, Z. Ghiorghiu, R. Macovei P065 - Predicting bacteremic urinary tract infection in community setting: A prospective observational study S. Nimitvilai, K. Jintanapramote, S. Jarupongprapa P066 - Eight-year analysis of acinetobacter spp. monobacteremia in surgical and medical intensive care units at university hospital in Lithuania D. Adukauskiene, D. Valanciene P067 - Group A and group B streptococcal infections in intensive care unit â€" our experience in a tertiary centre G. Bose, V. Lostarakos, B. Carr P068 - Improved detection of spontaneous bacterial peritonitis by uritopâ€‰+â€‰tm strip test and inoculation of blood culture bottles with ascitic fluid S. Khedher, A. Maaoui, A. Ezzamouri, M. Salem P069 - Increased risk of cellulitis in patients with congestive heart failure: a population based cohort study J. Chen P070 - Outcomes of severe cellulitis and necrotizing fasciitis in the critically ill D. R. Cranendonk, L. A. Van Vught, M. A. Wiewel, O. L. Cremer, J. Horn, M. J. Bonten, M. J. Schultz, T. Van der Poll, W. J. Wiersinga P071 - Botulism outbreak associated with people who inject drugs (PWIDs) in Scotland. M. Day, G. Penrice, K. Roy, P. Robertson, G. Godbole, B. Jones, M. Booth, L. Donaldson P072 - Surveillance of ESBL-producing enterobacteriaceae fecal carriers in the ICU Y. Kawano, H. Ishikura P073 - Prevalence of ESBL and carbapenemase producing uropathogens in a newly opened hospital in south India S. Sreevidya, N. Brahmananda Reddy, P. Muraray Govind, R. Pratheema, J. Devachandran Apollo Speciality Hospital - OMR, Chennai, India P074 - Prevalence, risk factors and outcomes of methicillin-resistant staphylococcus aureus nasal colonization in critically ill patients H. Al-Dorzi, M. Almutairi, B. Alhamadi, A. Crizaldo Toledo, R. Khan, B. Al Raiy, Y. Arabi P075 - Multidrug-resistant Acinetobacter baumannii infection in intensive care unit patients in a hospital with building construction: Is there an association? H. Talaie P076 - Multidrug-resistant organisms in a Dutch ICU J. A. Van Oers, A. Harts, E. Nieuwkoop, P. Vos P077 - Epidemiology and risk factors of ICU acquired infections caused by multidrug-resistant gram negative bacilli Y. Boussarsar, F. Boutouta, S. Kamoun, I. Mezghani, S. Koubaji, A. Ben Souissi, A. Riahi, M. S. Mebazaa P078 - Improving outcomes of severe infections by multidrug-resistant pathogens with polyclonal IgM-enriched immunoglobulins E. Giamarellos-Bourboulis, N. Tziolos, C. Routsi, C. Katsenos, I. Tsangaris, I. Pneumatikos, G. Vlachogiannis, V. Theodorou, A. Prekates, E. Antypa, V. Koulouras, N. Kapravelos, C. Gogos, E. Antoniadou, K. Mandragos, A. Armaganidis P079 - Must change the medical practice in ICU? A. R. Robles Caballero, B. Civantos, J. C. Figueira, J. LÃ³pez P080 - Mediterranean spotted fever in an infectious diseases intensive care unit A. Silva-Pinto, F. Ceia, A. Sarmento, L. Santos P081 - Clinical features and outcomes of patients with Middle East respiratory syndrome requiring admission to a saudi intensive care unit: A retrospective analysis of 31 cases G. Almekhlafi, Y. Sakr P082 - The ICU response to a hospital outbreak of Middle East respiratory syndrome coronavirus infection H. Al-Dorzi, R. Khan, S. Baharoon, A. Aldawood, A. Matroud, J. Alchin, S. Al Johani, H. Balkhy, Y. Arabi P083 - Middle East respiratory syndrome: Surveillance data analysis S. Alsolamy, S. Y. Yousif, B. O. Alotabi, A. S. Alsaawi P085 - Use of Taqman array card molecular diagnostics in severe pneumonia: A case series J. Ang, MD Curran, D. Enoch, V. Navapurkar, A. Conway Morris P086 - â€˜BUNSâ€™: An investigation protocol improves the ICU management of pneumonia R. Sharvill, J. Astin P087 - Pneumonia in patients following secondary peritonitis: epidemiological features and impact on mortality M. Heredia-RodrÃguez, E. GÃ³mez-SÃ¡nchez, M. T. PelÃ¡ez-JareÃ±o, E. GÃ³mez-Pesquera, M. Lorenzo-LÃ³pez, P. Liu-Zhu, M. AragÃ³n-Camino, A. HernÃ¡ndez-Lozano, A. SÃ¡nchez-LÃ³pez, E. Ãlvarez-Fuente, E. Tamayo P088 - The use of the â€œCURB-65 scoreâ€ by emergency room clinicians in a large teaching hospital J. Patel, C. Kruger P089 - Incidence of community acquired pneumonia with viral infection in mechanically ventilated patients in the medical intensive care unit J. Oâ€™Neal, H. Rhodes, J. Jancik P090 - The SAATELLITE Study: Prevention of S aureus Nosocomial Pneumonia (NP) with MEDI4893, a Human Monoclonal Antibody (mAb) Against S aureus B. FranÃ§ois, P. F. Laterre, P. Eggimann, A. Torres, M. SÃ¡nchez, P. F. Dequin, G. L. Bassi, J. Chastre, H. S. Jafri P091 - Risk factors and microbiological profile for nosocomial infections in trauma patients M. Ben Romdhane, Z. Douira, S. Kamoun, M. Bousselmi, A. Ben Souissi, Y. Boussarsar, A. Riahi, M.S. Mebazaa P092 - Correlation between percentages of ventilated patients developed vap and use of antimicrobial agents in ICU patients. A. Vakalos, V. Avramidis P093 - A comparison of two ventilator associated pneumonia surveillance techniques T. H. Craven, G. Wojcik, K. Kefala, J. McCoubrey, J. Reilly, R. Paterson, D. Inverarity, I. Laurenson, T. S. Walsh P094 - Lung ultrasound before and after fiberbronchoscopy - modifications may improve ventilator-associated pneumonia diagnosis S. Mongodi, B. Bouhemad, A. Orlando, A. Stella, G. Via, G. Iotti, A. Braschi, F. Mojoli P095 - Comparing the accuracy of predictors of mortality in ventilator-associated pneumonia M. Haliloglu, B. Bilgili, U. Kasapoglu, I. Sayan, M. SÃ¼zer Aslan, A. YalcÄ±n, I. Cinel P096 - Impact of pRBCs transfusion on percentage of ventilated patients developed VAP in ICU patients A. Vakalos, V. Avramidis P097 - The impact of a series of interventions on the rate of ventilator associated pneumonia in a large teaching hospital H. E. Ellis, K. Bauchmuller, D. Miller, A Temple P098 - The EVADE study: Prevention of Nosocomial Pneumonia (NP) caused by P aeruginosa with MEDI3902, a Novel Bispecific Monoclonal Antibody, against P aeruginosa virulence factors J. Chastre, B. FranÃ§ois, A. Torres, C. E. Luyt, M. SÃ¡nchez, M. Singer, H. S. Jafri P099 - Short-term inhaled colistin adjunctive therapy for ventilator-associated pneumonia Y. Nassar, M. S. Ayad P100 - Effect of aerosolised colistin on weaning from mechanical ventilation A. Trifi, S. Abdellatif, F. Daly, R. Nasri, S. Ben Lakhal P101 - Septic shock is an independent risk factor for colistin-induced severe acute kidney injury: a retrospective cohort study B. Bilgili, M. Haliloglu, F. Gul, I. Cinel P102 - Nosocomial pneumonia - emphasis on inhaled tobramycin A. Kuzovlev, A. Shabanov, S. Polovnikov, V. Moroz P103 - In vitro evaluation of amikacin inhale and commercial nebulizers in a mechanical ventilator N. Kadrichu, T. Dang, K. Corkery, P. Challoner P104 - The effects of nebulized amikacin/fosfomycin and systemic meropenem on severe amikacin-resistant meropenem-susceptible P.aeruginosa pneumonia G. Li Bassi, E. Aguilera, C. Chiurazzi, C. Travierso, A. Motos, L. Fernandez, R. Amaro, T. Senussi, F. Idone, J. Bobi, M. Rigol, A. Torres P105 - Optimization of gentamicin peak concentrations in critically ill patients C. J. Hodiamont, N. P. Juffermans, J. M. Janssen, C. S. Bouman, R. A. MathÃ´t, M. D. De Jong, R. M. Van Hest P106 - Systematic review of cefepime induced neurotoxicity L. Payne, G. L. Fraser P107 - UnasynÂ® causes QT prolongation during treatment of intensive care patients B. Tudor, M. Lahner, G. Roth, C. Krenn P108 - Comparative study between teicoplanin and vancomycin in methicillin-resistant staphylococcus aureus (mrsa) infectious of toxicological intensive care unit (ticu) patients â€" Tehran, Iran H. Talaie P109 - Phage therapy against antimicrobial resistance, design of the first clinical study phagoburn P. Jault, J. Gabard, T. Leclerc, S. Jennes, Y. Que, A. Rousseau, F. Ravat P110 - Antibiotic dosing errors in critically ill patients with severe sepsis or septic shock H. Al-Dorzi, A. Eissa, S. Al-Harbi, T. Aldabbagh, R. Khan, Y. Arabi P111 - Does empiric antifungal therapy improve survival in septic critically ill patients? (immunocompromised excluded) A. Trifi, S. Abdellatif, F. Daly, R. Nasri, S. Ben Lakhal P112 - Neurocysticercosis-Qatar experience F. Paramba, N. Purayil, V. Naushad, O. Mohammad, V. Negi, P. Chandra P113 - Early indicators in acute haemorrhagic shock A. Kleinsasser P114 - Filtering of red blood cells reduces the inflammatory response of pulmonary cells in an in vitro model of mechanical ventilation M. R. Witrz, J. F. Buchner-Doeven, A. M. Tuip-de Boer, J. C. Goslings, N. P. Juffermans P115 - Microparticles from red blood cell transfusion induce a pro-coagulant and pro-inflammatory endothelial cell response M. Van Hezel, M. Straat, A Boing, R Van Bruggen, N Juffermans P116 - The contribution of cytokines on thrombosis development during hospitalization in ICU D. Markopoulou, K. Venetsanou, V. Kaldis, D. Koutete, D. Chroni, I. Alamanos P117 - Prophylactic enoxaparin dosing and adjustment through anti-xa monitoring in an inpatient burn unit L. Koch, J. Jancik, H. Rhodes, E. Walter P118 - Determination of optimal cut-off values of haemoglobin, platelet count and fibrinogen at 24Â hours after injury associated with mortality in trauma patients K. Maekawa, M. Hayakawa, S. Kushimoto, A. Shiraishi, H. Kato, J. Sasaki, H. Ogura, T. Matauoka, T. Uejima, N. Morimura, H. Ishikura, A. Hagiwara, M. Takeda P119 - Trauma-induced coagulopathy - prothrombin complex concentrate vs fresh frozen plasma O. Tarabrin, S. Shcherbakow, D. Gavrychenko, G. Mazurenko, V. Ivanova, O. Chystikov P120 - First study to prove the superiority of prothrombin complex concentrates on mortality rate over fresh frozen plasma in patients with acute bleeding C. Plourde, J. Lessard, J. Chauny, R. Daoust P121 - Prothrombin complex concentrate vs fresh frozen plasma in obstetric massive bleeding S. Shcherbakow, O. Tarabrin, D. Gavrychenko, G. Mazurenko, O. Chystikov P122 - Impact of FFP transfusion on VAP in ICU patients A. Vakalos, V. Avramidis P123 - Preoperative platelet function test and the thrombin generation assay are predictive for blood loss after cardiac surgery L. Kropman, L. In het Panhuis, J. Konings, D. Huskens, E. Schurgers, M. Roest, B. De Laat, M. Lance P124 - Rotational thromboelastometry versus standard coagulation tests before surgical interventions M. Durila, P. Lukas, M. Astraverkhava, J. Jonas P125 - Correction of impaired clot quality and stability by fibrinogen and activated prothrombin complex concentrate in a model of severe thrombocytopenia I. Budnik, B. Shenkman P126 - Assessment of point-of-care prothrombin time analyzer as a monitor after cardiopulmonary bypass H. Hayami, Y. Koide, T. Goto P127 - Disseminated intravascular coagulation (dic) is underdiagnosed in critically ill patients: do we need d-dimer measurements? R. Iqbal, Y. Alhamdi, N. Venugopal, S. Abrams, C. Downey, C. H. Toh, I. D. Welters P128 - Validity of the age-adjusted d-dimer cutoff in patients with COPD B. Bombay, J. M. Chauny, R. D. Daoust, J. L. Lessard, M. M. Marquis, J. P. Paquet P129 - A scoping review of strategies for prevention and management of bleeding following paediatric cardiopulmonary bypass surgery K. Siemens, D. Sangaran, B. J. Hunt, A. Durward, A. Nyman, I. A. Murdoch, S. M. Tibby P130 - Nadir hemoglobulin during cardiopulmonary bypass: impact on postoperative morbidity and mortality F. Ampatzidou, D. Moisidou, E. Dalampini, M. Nastou, E. Vasilarou, V. Kalaizi, H. Chatzikostenoglou, G. Drossos P131 - Red blood cell transfusion do not influence the prognostic value of RDW in critically ill patients S. Spadaro, A. Fogagnolo, T. Fiore, A. Schiavi, V. Fontana, F. Taccone, C. Volta P132 - Reasons for admission in the paediatric intensive care unit and the need for blood and blood products transfusions E. Chochliourou, E. Volakli, A. Violaki, E. Samkinidou, G. Evlavis, V. Panagiotidou, M. Sdougka P133 - The implementation of a massive haemorrhage protocol (mhp) for the management of major trauma: a ten year, single-centre study R. Mothukuri, C. Battle, K. Guy, G. Mills, P. Evans P134 - An integrated major haemorrhage protocol for pre-hospital and retrieval medical teams J. Wijesuriya, S. Keogh P135 - The impact of transfusion thresholds on mortality and cardiovascular events in patients with cardiovascular disease (non-cardiac surgery): a systematic review and meta-analysis A. Docherty, R. Oâ€™Donnell, S. Brunskill, M. Trivella, C. Doree, L. Holst, M. Parker, M. Gregersen, J. Almeida, T. Walsh, S. Stanworth P136 - The relationship between poor pre-operative immune status and outcome from cardiac surgery is specific to the peri-operative antigenic threat S. Moravcova, J. Mansell, A. Rogers, R. A. Smith, C. Hamilton-Davies P137 - Impact of simple clinical practice guidelines for reducing post-operative atrial fibrillation after cardiac surgery. A. Omar, M. Allam, O. Bilala, A. Kindawi, H. Ewila P138 - Dexamethasone administration during cardiopulmonary bypass has no beneficial effects on elective postoperative cardiac surgery patients F. Ampatzidou, D. Moisidou, M. Nastou, E. Dalampini, A. Malamas, E. Vasilarou, G. Drossos P139 - Intra-aortic balloon counterpulsation in patients undergoing cardiac surgery (IABCS): preliminary results G. Ferreira, J. Caldas, J. Fukushima, E. A. Osawa, E. Arita, L. Camara, S. Zeferino, J. Jardim, F. Gaioto, L. Dallan, F. B. Jatene, R. Kalil Filho, .F Galas, L. A. Hajjar P140 - Effects of low-dose atrial natriuretic peptide infusion on cardiac surgery-associated acute kidney injury C. Mitaka, T. Ohnuma, T. Murayama, F. Kunimoto, M. Nagashima, T. Takei, M. Tomita P141 - Acute kidney injury influence on high sensitive troponin measurements after cardiac surgery A. Omar, K. Mahmoud, S. Hanoura, S. Sudarsanan, P. Sivadasan, H. Othamn, Y. Shouman, R. Singh, A. Al Khulaifi P142 - Complex evaluation of endothelial dysfunction markers for prognosis of outcomes in patients undergoing cardiac surgery I. Mandel, S. Mikheev, I. Suhodolo, V. Kiselev, Y. Svirko, Y. Podoksenov P143 - New-onset atrial fibrillation in intensive care: incidence, management and outcome S. A. Jenkins, R. Griffin P144 - One single spot measurement of the sublingual microcirculation during acute pulmonary hypertension in a pig model of shock M. S. Tovar Doncel, A. Lima, C. Aldecoa, C. Ince P145 - Assessment of levosimendan as a therapeutic option to recruit the microcirculation in cardiogenic shock â€" initial experience in cardiac ICU A. Taha, A. Shafie, M. Mostafa, N. Syed, H. Hon P146 - Terlipressin vs. norepinephrine in the Potential Multiorgan Donor(PMD) F. Righetti, E. Colombaroli, G. Castellano P147 - Echocardiography in the potential heart donor exposed to substitution hormonotherapy F. Righetti, E. Colombaroli P148 - Machine learning can reduce rate of monitor alarms M. Hravnak, L. C. Chen, A. D. Dubrawski, G. C. Clermont, M. R. Pinsky P149 - Peripherally inserted central catheters placed in the ICU S. Gonzalez, D. Macias, J. Acosta, P. Jimenez, A. Loza, A. Lesmes, F. Lucena, C. Leon P150 - Recordings of abnormal central venous pressure waveform morphology during an episode of pulmonary hypertension in a porcine shock model M. S. Tovar Doncel, C. Ince, C. Aldecoa, A. Lima P151 - Ultrasound guided central venous access technique among French intensivists M. Bastide, J. Richecoeur, E. Frenoy, C. Lemaire, B. Sauneuf, F. Tamion, S. Nseir, D. Du Cheyron, H. Dupont, J. Maizel P152 - Predictive ability of the Pv-aCO2 gap in patients with shock M. Shaban, R. Kolko, N. Salahuddin, M. Sharshir, M. AbuRageila, A. AlHussain P153 - Comparison of echocardiography and pulmonary artery catheter measurements of hemodynamic parameters in critical ill patients P. Mercado, J. Maizel, L. Kontar, D. Titeca, F. Brazier, A. Riviere, M. Joris, T. Soupison, B. De Cagny, M. Slama P154 - The volume clamp method for noninvasive cardiac output measurement in postoperative cardiothoracic surgery patients: a comparison with intermittent pulmonary artery thermodilution J. Wagner, A. KÃ¶rner, M. Kubik, S. Kluge, D. Reuter, B. Saugel P155 - Hemodynamic monitoring in patients with septic shock (SS) â€" CPCCO (continuous pulse contour cardiac output) vs. TEE (transesophageal echocardiography) E. Colombaroli, F. Righetti, G. Castellano P156 - Cardiac output measurement with transthoracic echocardiography in critically ill patients: a pragmatic clinical study T. Tran, D. De Bels, A. Cudia, M. Strachinaru, P. Ghottignies, J. Devriendt, C. Pierrakos P157 - Left ventricular outflow tract velocity time integral correlates with stroke volume index in mechanically ventilated patients Ã". MartÃnez GonzÃ¡lez, R. Blancas, J. LujÃ¡n, D. Ballesteros, C. MartÃnez DÃaz, A. NÃºÃ±ez, C. MartÃn Parra, B. LÃ³pez Matamala, M. Alonso FernÃ¡ndez, M. Chana P158 - Transpulmonary thermodilution (TPTD) derived from femoral vs. jugular central venous catheter: validation of a previously published correction formula and a proprietary correction formula for global end-diastolic volume index (GEDVI) W. Huber, M. Eckmann, F. Elkmann, A. Gruber, I. Klein, R. M. Schmid, T. Lahmer P160 - Dynamic arterial elastance calculated with lidcoplus monitor does not predict changes in arterial pressure after a fluid challenge in postsurgical patients D. Bastoni, H. Aya, L. Toscani, L. Pigozzi, A. Rhodes, M. Cecconi P159 - Venous return driving pressure and resistance in acute blood volume changes P. W. Moller, S. Sondergaard, S. M. Jakob, J. Takala, D. Berger P160 - Dynamic arterial elastance calculated with lidcoplus monitor does not predict changes in arterial pressure after a fluid challenge in postsurgical patients D. Bastoni, H. Aya, L. Toscani, L. Pigozzi, A. Rhodes, M. Cecconi P161 - Analysis of duration of post-operative goal-directed therapy protocol C. Ostrowska, H. Aya, A. Abbas, J. Mellinghoff, C. Ryan, D. Dawson, A. Rhodes, M. Cecconi P162 - Hemodynamic optimization â€" back to square one? M. Cronhjort, O. Wall, E. Nyberg, R. Zeng, C. Svensen, J. MÃ¥rtensson, E. Joelsson-Alm P163 - Effectiveness of fluid thoracic content measurement by bioimpedance guiding intravascular volume optimization in patients with septic shock M. Aguilar Arzapalo, L. Barradas, V. Lopez, M. Cetina P164 - A systematic review on the role of internal jugular vein ultrasound measurements in assessment of volume status in critical shock patients N. Parenti, C. Palazzi, L. A. Amidei, F. B. Borrelli, S. C. Campanale, F. T. Tagliazucchi, G. S. Sedoni, D. L. Lucchesi, E. C. Carella, A. L Luciani P165 - Importance of recognizing dehydration in medical Intensive Care Unit M. Mackovic, N. Maric, M. Bakula P166 - Effect of volume for a fluid challenge in septic patients H. Aya, A. Rhodes, R. M. Grounds, N. Fletcher, M. Cecconi P167 - Fluid bolus practices in a large Australian intensive care unit B. Avard, P. Zhang P168 - Liberal late fluid management is associated with longer ventilation duration and worst outcome in severe trauma patients: a retrospective cohort of 294 patients M. Mezidi, J. Charbit, M. Ould-Chikh, P. Deras, C. Maury, O. Martinez, X. Capdevila P169 - Association of fluids and outcomes in emergency department patients hospitalized with community-acquired pneumonia P. Hou, W. Z. Linde-Zwirble, I. D. Douglas, N. S. Shapiro P170 - Association of positive fluid balance with poor outcome in medicosurgical ICU patients A. Ben Souissi, I. Mezghani, Y. Ben Aicha, S. Kamoun, B. Laribi, B. Jeribi, A. Riahi, M. S. Mebazaa P171 - Impact of fluid balance to organ dysfunction in critically ill patients C. Pereira, R. Marinho, R. Antunes, A. Marinho P172 - Volume bolus in ICU patients: do we need to balance our crystalloids? M. Crivits, M. Raes, J. Decruyenaere, E. Hoste P173 - The use of 6Â % HES solution do not reduce total fluid requirement in the therapy of patients with burn shock V. Bagin, V. Rudnov, A. Savitsky, M. Astafyeva, I. Korobko, V. Vein P174 - Electron microscopic assessment of acute kidney injury in septic sheep resuscitated with crystalloids or different colloids T. Kampmeier, P. Arnemann, M. Hessler, A. Wald, K. Bockbreder, A. Morelli, H. Van Aken, S. Rehberg, C. Ertmer P175 - Alterations of conjunctival microcirculation in a sheep model of haemorrhagic shock and resuscitation with 0.9Â % saline or balanced tetrastarch P. Arnemann, M. Hessler, T. Kampmeier, S. Rehberg, H. Van Aken, C. Ince, C. Ertmer P176 - A single centre nested pilot study investigating the effect of using 0.9Â % saline or Plasma-Lyte 148 Â® as crystalloid fluid therapy on gastrointestinal feeding intolerance in mechanically ventilated patients receiving nasogastric enteral nutrition S. Reddy, M. Bailey, R. Beasley, R. Bellomo, D. Mackle, A. Psirides, P. Young P177 - A single centre nested pilot study investigating the effect on post-operative bleeding of using 0.9Â % saline or Plasma-LyteÂ® 148 as crystalloid fluid therapy in adults in ICU after heart surgery S. Reddy, M. Bailey, R. Beasley, R. Bellomo, D. Mackle, P. Young P178 - Extreme hypernatremia and sepsis in a patient with Huntingtonâ€™s dementia: a conundrum in fluid management H. Venkatesh, S. Ramachandran, A. Basu, H. Nair P179 - Diagnosis and management of severe hypernatraemia in the critical care setting S. Egan, J. Bates P180 - Correlation between arterial blood gas and electrolyte disturbances during hospitalization and outcome in critically ill patients S. Oliveira, N. R. Rangel Neto, F. Q. Reis P181 - Missing the â€œIâ€ in MUDPILES â€" a rare cause of high anion gap metabolic acidosis (HAGMA) C. P. Lee, X. L. Lin, C. Choong, K. M. Eu, W. Y. Sim, K. S. Tee, J. Pau, J. Abisheganaden P182 - Plasma NGAL and urinary output: potential parameters for early initiation of renal replacement therapy K. Maas, H. De Geus P183 - Renal replacement therapy for critically ill patients: an intermittent continuity E. Lafuente, R. Marinho, J. Moura, R. Antunes, A. Marinho P184 - A survey of practices related to renal replacement therapy in critically ill patients in the north of England. T. E. Doris, D. Monkhouse, T. Shipley, S. Kardasz, I Gonzalez P185 - High initiation creatinine associated with lower 28-day mortality in critically ill patients necessitating continuous renal replacement therapy S. Stads, A. J. Groeneveld P186 - The impact of Karnofsky performance scale on outcomes in acute kidney injury patients receiving renal replacement therapy on the intensive care unit I. Elsayed, N. Ward, A. Tridente, A. Raithatha P187 - Severe hypophosphatemia during citrate-anticoagulated CRRT A. Steuber, C. Pelletier, S. Schroeder, E. Michael, T. Slowinski, D. Kindgen-Milles P188 - Citrate regional anticoagulation for post dilution continuous renal replacement therapy S. Ghabina P189 - Citrate 18Â mmol/l improves anticoagulation during RRT with adsorbing filters F. Turani, A. Belli, S. Busatti, G. Barettin, F. Candidi, F. Gargano, R. Barchetta, M. Falco P190 - Calcium gluconate instead of calcium chloride in citrate-anticoagulated CVVHD O. Demirkiran, M. Kosuk, S. Bozbay P191 - Enhanced clearance of interleukin-6 with continuous veno-venous haemodialysis (CVVHD) using Ultraflux EMiC2 vs. Ultraflux AV1000S V. Weber, J. Hartmann, S. Harm, I. Linsberger, T. Eichhorn, G. Valicek, G. Miestinger, C. Hoermann P192 - Removal of bilirubin with a new adsorbent system: in vitro kinetics S. Faenza, D. Ricci, E. Mancini, C. Gemelli, A. Cuoghi, S. Magnani, M. Atti P193 - Case series of patients with severe sepsis and septic shock treated with a new extracorporeal sorbent T. Laddomada, A. Doronzio, B. Balicco P194 - In vitro adsorption of a broad spectrum of inflammatory mediators with CytoSorbÂ® hemoadsorbent polymer beads M. C. Gruda, P. Oâ€™Sullivan, V. P. Dan, T. Guliashvili, A. Scheirer, T. D. Golobish, V. J. Capponi, P. P. Chan P195 - Observations in early vs. late use of cytosorb therapy in critically ill patients K. Kogelmann, M. DrÃ¼ner, D. Jarczak P196 - Oxiris membrane decreases endotoxin during rrt in septic patients with basal EAAâ€‰>â€‰0, 6 F. Turani, A. B. Belli, S. M. Martni, V. C. Cotticelli, F. Mounajergi, R. Barchetta P197 - An observational prospective study on the onset of augmented renal clearance: the first report S. Morimoto, H. Ishikura P198 - An ultrasound- guided algorithm for the management of oliguria in severe sepsis I. Hussain, N. Salahuddin, A. Nadeem, K. Ghorab, K. Maghrabi P199 - Ultrasound in acute kidney injury (aki). First findings of farius, an education-programme in structural ultrasonography S. K. Kloesel, C. Goldfuss, A. Stieglitz, A. S. Stieglitz, L. Krstevska, G. Albuszies P200 - Effectiveness of renal angina index score predicting acute kidney injury on critically ill patients M. Aguilar Arzapalo, L. Barradas, V. Lopez, A. Escalante, G. Jimmy, M. Cetina P201 - Time length below blood pressure thresholds and progression of acute kidney injury in critically ill patients with or without sepsis: a retrospective, exploratory cohort study J. Izawa, T. Iwami, S. Uchino, M. Takinami, T. Kitamura, T. Kawamura P202 - Anaemia does not affect renal recovery in acute kidney injury J. G. Powell-Tuck, S. Crichton, M. Raimundo, L. Camporota, D. Wyncoll, M. Ostermann P203 - Estimated glomerular filtration rate based on serum creatinine: actual practice in Dutch ICUâ€™s A. Hana, H. R. De Geus P204 - Comparison of estimated glomerular filtration rate calculated by mdrd, ckd-epi-serum-creatinine and ckd-epi-cystatin-c in adult critically ill patients H. R. De Geus, A. Hana P205 - Early diagnosis of septic acute kidney injury in medical critical care patients with a urine cell cycle arrest marker: insulin like growth factor binding protein-7 (IGFBP-7) M. Aydogdu, N. Boyaci, S. Yuksel, G. Gursel, A. B. Cayci Sivri P206 - Urinary neutrophil gelatinase-associated lipocalin as early biomarker of severe acute kidney injury in intensive care J. Meza-MÃ¡rquez, J. Nava-LÃ³pez, R. Carrillo-Esper P207 - Shrunken pore syndrome is associated with a sharp rise in mortality in patients undergoing elective coronary artery bypass grafting A. Dardashti, A. Grubb P208 - The biomarker nephrocheckâ„¢ can discriminate the septic shock patients with an akin 1 or 2 acute renal failure who will not progress toward the akin 3 level J. Maizel, M. Wetzstein, D. Titeca, L. Kontar, F. Brazier, B. De Cagny, A. Riviere, T. Soupison, M. Joris, M. Slama P209 - A worldwide multicentre evaluation of acute kidney injury in septic and non-septic critically ill patients: the intensive care over nations (icon) audit E. Peters, H. Njimi, P. Pickkers, J. L. Vincent P210 - Does enhanced recovery after surgery reduce the incidence of acute kidney injury in those undergoing major gynae-oncological surgery? M. Waraich, J. Doyle, T. Samuels, L. Forni P211 - Identification of risk factors for the development of acute kidney injury after lower limb arthroplasty N. Desai, R. Baumber, P. Gunning, A. Sell P212 - Incidences and associations of acute kidney injury after major trauma S. Lin, H. Torrence, M. Oâ€™Dwyer, C. Kirwan, J. Prowle P213 - Acute kidney injury of major trauma patients T Kim P214 - Trajectory of serum creatinine after major surgery and the diagnosis of acute kidney injury M. E. Oâ€™Connor, R. W. Hewson, C. J. Kirwan, R. M. Pearse, J. Prowle P215 - Epidemiology of acute kidney injury after cardiac surgery. A single center retrospective study S. Hanoura, A. Omar, H. Othamn, S. Sudarsanan, M. Allam, M. Maksoud, R. Singh, A. Al Khulaifi P216 - Post-operative acute kidney injury after major non-cardiac surgery and its association with death in the following year M. E. Oâ€™Connor, R. W. Hewson, C. J. Kirwan, R. M. Pearse, J. Prowle P217 - Factors affecting acute renal failure in intensive care unit and effect of these factors on mortality O. Uzundere, D. Memis, M. Ãnal, A., N. Turan P218 - Results of the live kidney transplantations according to national data of turkish organ and tissue information system M. A. Aydin, H. Basar, I. Sencan, A. Kapuagasi, M. Ozturk, Z. Uzundurukan, D. Gokmen, A. Ozcan, C. Kaymak P219 - Anaesthesia procedure and intensive therapy in patients with neck phlegmon V. A. Artemenko, A. Budnyuk P220 - Nasal high flow oygen for acute respiratory failure: a systematic review R. Pugh, S. Bhandari P221 - Setting optimal flow rate during high flow nasal cannula support: preliminary results T. Mauri, C. Turrini, T. Langer, P. Taccone, C. A. Volta, C. Marenghi, L. Gattinoni, A. Pesenti P222 - Dose to dose consistency across two different gas flow rates using cystic fibrosis and normal adult breathing profiles during nasal high flow oxygen therapy L. Sweeney, A . Oâ€™ Sullivan, P. Kelly, E. Mukeria, R. MacLoughlin P223 - Final results of an evaluation of airway medix closed suction system compared to a standard closed suction system M. Pfeffer, J. T. Thomas, G. B. Bregman, G. K. Karp, E. K. Kishinevsky, D. S. Stavi, N. A. Adi P224 - Different cuff materials and different leak tests - one size does not fit all T. Poropat, R. Knafelj P225 - Observational study on the value of the cuff-leak test and the onset of upper airway obstruction after extubation E. Llopart, M. Batlle, C. De Haro, J. Mesquida, A. Artigas P226 - A device for emergency transtracheal lung ventilation D. Pavlovic, L. Lewerentz, A. Spassov, R. Schneider P227 - Long-term outcome and health-related quality of life in patients discharged from the intensive care unit with a tracheostomy and with or without prolonged mechanical ventilation S. De Smet, S. De Raedt, E. Derom, P Depuydt, S. Oeyen, D. Benoit, J. Decruyenaere P228 - Ultrasound-guided percutaneous dilational tracheostomy versus bronchoscopy-guided percutaneous dilational tracheostomy in critically ill patients (trachus): a randomized clinical trial A. Gobatto, B. Bese, P. Tierno, L. Melro, P. Mendes, F. Cadamuro, M. Park, L. M. Malbouisson P229 - Is it safe to discharge patients with tracheostomy from the ICU to the ward? B. C. Civanto, J. L. Lopez, A. Robles, J. Figueira, S. Yus, A. Garcia P230 - The application of tracheostomy in children in ICU A. Oglinda, G. Ciobanu, C. Oglinda, L. Schirca, T. Sertinean, V. Lupu P231 - The impact of passive humidifiers on aerosol drug delivery during mechanical ventilation P. Kelly, A. Oâ€™Sullivan, L. Sweeney, R. MacLoughlin P232 - Evaluation of vibrating mesh and jet nebuliser performance at two different attachment setups in line with a humidifier nebuliser system A. Oâ€™Sullivan, P. Kelly, L. Sweeney, E. Mukeria, M. Wolny, R. MacLoughlin P233 - Psv-niv versus cpap in the treatment of acute cardiogenic pulmonary edema A. Pagano, F. Numis, G. Vison, L. Saldamarco, T. Russo, G. Porta, F. Paladino P234 - Noninvasive ventilation in patients with haematologic malignancy: a retrospective review C. Bell, J. Liu, J. Debacker, C. Lee, E. Tamberg, V. Campbell, S. Mehta P235 - Use of non-invasive ventilation in infectious diseases besides classical indications A. Silva-Pinto, A. Sarmento, L. Santos P236 - The impact of fragility on noninvasive mechanical ventilation application and results in the ICU Ã. Kara, F. YÃ½ldÃ½rÃ½m, A. Zerman, Z. GÃ¼llÃ¼, N. BoyacÃ½, B. BasarÃ½k Aydogan, Ãœ. GaygÃ½sÃ½z, K. GÃ¶nderen, G. ArÃ½k, M. Turkoglu, M. Aydogdu, G. Aygencel, Z. Ãœlger, G. Gursel P237 - Effects of metabolic alkalosis on noninvasive ventilation success and ICU outcome in patients with hypercapnic respiratory failure N. BoyacÃ½, Z. IsÃ½kdogan, Ã–. Ã–zdedeoglu, Z. GÃ¼llÃ¼, M. Badoglu, U. GaygÃ½sÃ½z, M. Aydogdu, G. Gursel P238 - Asynchrony index and breathing patterns of acute exacerbation copd patients assisted with noninvasive pressure support ventilation and neurally adjusted ventilatory assist N. Kongpolprom, C. Sittipunt P239 - High frequency jet ventilation for severe acute hypoxemia A. Eden, Y. Kokhanovsky, S. Bursztein â€" De Myttenaere, R. Pizov P240 - HFOV revisited: a 7Â year retrospective analysis of patients receiving HFOV who met oscillate trial entry criteria L. Neilans, N. MacIntyre P241 - Implementation of a goal-directed mechanical ventilation order set driven by respiratory therapists can improve compliance with best practices for mechanical ventilation M. Radosevich, B. Wanta, V. Weber, T. Meyer, N. Smischney, D. Brown, D. Diedrich P242 - A reduction in tidal volumes for ventilated patients on ICU calculated from IBW. can it minimise mortality in comparison to traditional strategies? A . Fuller, P. McLindon, K. Sim P243 - Predictive value of lung aeration scoring using lung ultrasound in weaning failure M. Shoaeir, K. Noeam, A. Mahrous, R. Matsa, A. Ali P244 - Conventional versus automated weaning from mechanical ventilation using SmartCareâ„¢ C. Dridi, S. Koubaji, S. Kamoun, F. Haddad, A. Ben Souissi, B. Laribi, A. Riahi, M. S. Mebazaa P245 - Ultrasonographic evaluation protocol for weaning from mechanichal ventilation A. PÃ©rez-Calatayud, R. Carrillo-Esper, A. Zepeda-Mendoza, M. Diaz-Carrillo, E. Arch-Tirado P246 - Diaphragm ultrasonography: a method for weaning patients from mechanical ventilation S. Carbognin, L. Pelacani, F. Zannoni, A. Agnoli, G. Gagliardi P247 - Dorsal diaphragmatic excursion tracks transpulmonary pressure in ventilated ARDS patients: a potential non-invasive indicator of lung recruitment? R. Cho, A. Adams, S. Lunos, S. Ambur, R. Shapiro, M. Prekker P248 - Pulse oximetry in the icu patient: is the perfusion index of any value? M. Thijssen, L. Janssen, N. Foudraine P249 - Ventilation is a better assessment of respiratory status than EtCO2 C. J. Voscopoulos, J. Freeman P250 - Evaluation of the relationship between non-invasive minute ventilation and end-tidal CO2 in patients undergoing general vs spinal anesthesia C. J. Voscopoulos, J. Freeman, E. George P251 - Respiratory volume monitoring provides early warning of respiratory depression and can be used to reduce false alarms in non-intubated patients C. J. Voscopoulos, D. Eversole, J. Freeman, E. George P252 - P/i index: a predictive edi-derived weaning index during nava S. Muttini, R. Bigi, G. Villani, N. Patroniti P253 - Adequacy of ventilation in patients receiving opioids in the post anesthesia care unit: minute ventilation versus respiratory rate G. Williams, C. J. Voscopoulos, J. Freeman, E. George P254 - Comparison of regional and global expiratory time constants measured by electrical impedance tomography (EIT) A. Waldmann, S. BÃ¶hm, W. Windisch, S. Strassmann, C. Karagiannidis P255 - Electrical impedance tomography: robustness of a new pixel wise regional expiratory time constant calculation A. Waldmann, S. BÃ¶hm, W. Windisch, S. Strassmann, C. Karagiannidis P256 - Validation of regional and global expiratory time constant measurement by electrical impedance tomography in ards and obstructive pulmonary diseases C. K. Karagiannidis, A. W. Waldmann, S. B. BÃ¶hm, S. Strassmann, W. W. Windisch P257 - Transpulmonary pressure in a model with elastic recoiling lung and expanding chest wall P. Persson, S. Lundin, O. Stenqvist P258 - Lactate in pleural and abdominal effusion G. Porta, F. Numis, C. S. Serra, A. P. Pagano, M. M. Masarone, L. R. Rinaldi, A. A. Amelia, M. F. Fascione, L. A. Adinolfi, E. R. Ruggiero P259 - Outcome of patients admitted to the intensive care with pulmonary fibrosis F. Asota, K. Oâ€™Rourke, S. Ranjan, P. Morgan P260 - Sedation and analgesia practice in extra-corporeal membrane oxygenation (ECMO)-treated patients with acute respiratory distress syndrome (ARDS): a retrospective study J. W. DeBacker, E. Tamberg, L. Oâ€™Neill, L. Munshi, L. Burry, E. Fan, S. Mehta P261 - Characteristics and outcomes of patients deemed not eligible when referred for veno-venous extracorporeal membrane oxygenation (vv-ECMO) S. Poo, K. Mahendran, J. Fowles, C. Gerrard, A. Vuylsteke P262 - The SAVE SMR for veno-arterial ECMO R. Loveridge, C. Chaddock, S. Patel, V. Kakar, C. Willars, T. Hurst, C. Park, T. Best, A. Vercueil, G. Auzinger P263 - A simplified score to predict early (48Â h) mortality in patients being considered for VA-ECMO A. Borgman, A. G. Proudfoot, E. Grins, K. E. Emiley, J. Schuitema, S. J. Fitch, G. Marco, J. Sturgill, M. G. Dickinson, M. Strueber, A. Khaghani, P. Wilton, S. M. Jovinge P264 - Lung function six months post extra corporeal membrane oxygenation (ECMO) for severe acute respiratory failure in adult survivors C. Sampson, S. Harris-Fox P265 - Bicarbonate dialysis removes carbon dioxide in hypoventilated rodents. M. E. Cove, L. H. Vu, A. Sen, W. J. Federspiel, J. A. Kellum P266 - Procalcitonin as predictor of primary graft dysfunction and mortality in post-lung transplantation C. Mazo Torre, J. Riera, S. Ramirez, B. Borgatta, L. Lagunes, J. Rello P267 - New molecular biomarkers of acute respiratory distress syndrome in abdominal sepsis A. K. Kuzovlev, V. Moroz, A. Goloubev, S. Polovnikov, S. Nenchuk P268 - Tight junctionâ€™s proteins claudin -5 and regulation by tnf in experimental murine lung injury model of ali/ards V. Karavana, C. Glynos, A. Asimakos, K. Pappas, C. Vrettou, M. Magkou, E. Ischaki, G. Stathopoulos, S. Zakynthinos P269 - Cell counts in endobronchial aspirate to assess airway inflammation in ARDS patients: a pilot study S. Spadaro, I. Kozhevnikova, F. Dalla Corte, S. Grasso, P. Casolari, G. Caramori, C. Volta P270 - Epidemiological and clinical profile of patients with acute respiratory distress syndrome in the surgical intensive care unit surgical, hospital JRA, Antananarivo T. Andrianjafiarinoa, T. Randriamandrato, T. Rajaonera P271 - Effect of high PEEP after recruitment maneuver on right ventricular function in ARDS. Is it good for the lung and for the heart? S. El-Dash, ELV Costa, MR Tucci, F Leleu, L Kontar, B. De Cagny, F. Brazier, D. Titeca, G. Bacari-Risal, J. Maizel, M. Amato, M. Slama P272 - Effect of recruitment maneuver on left ventricular systolic strain P. Mercado, J. Maizel, L. Kontar, D. Titeca, F. Brazier, A. Riviere, M. Joris, T. Soupison, B. De Cagny, S. El Dash, M. Slama P273 - Inhaled nitric oxide â€" is switching supplier cost effective? Remmington, A. Fischer, S. Squire, M. Boichat P274 - Epidemiological study of severe acute pancreatitis in Japan, comparison of the etiology and the patient outcomes on 1159 patients. H. Honzawa, H. Yasuda, T. Adati, S. Suzaki, M. Horibe, M. Sasaki, M. Sanui P275 - Extracorporeal liver support therapy. Experience in an intensive care unit R. Marinho, J. Daniel, H. Miranda, A. Marinho P276 - Accuracy of mortality prediction models in acute versus acute-on-chronic liver failure in the intensive care setting K. Milinis, M. Cooper, G. R. Williams, E. McCarron, S. Simants, I. Patanwala, I. Welters P277 - Risk of coronary artery disease in patients with chronic liver disease: a population based cohort study Y. Su P278 - 20Â years of liver transplantation in Santiago de Compostela (Spain). Experience review J. FernÃ¡ndez Villanueva, R. FernÃ¡ndez Garda, A. LÃ³pez Lago, E. RodrÃguez RuÃz, R. HernÃ¡ndez Vaquero, S. TomÃ© MartÃnez de Rituerto, E. Varo PÃ©rez P279 - Diarrhea is a risk factor for liver injury and may lead to intestinal failure associated liver disease in critical illness N. Lefel, F. Schaap, D. Bergmans, S. Olde Damink, M. Van de Poll P280 - Bowel care on the intensive care unit: constipation guideline compliance and complications K. Tizard, C. Lister, L. Poole P281 - Malnutrition assessed by phase angle determines outcomes in low risk cardiac surgery patients D. Ringaitiene, D. Gineityte, V. Vicka, I. Norkiene, J. Sipylaite P282 - Preoperative fasting times in an irish hospital A. Oâ€™Loughlin, V. Maraj, J. Dowling P283 - Costs and final outcome of early x delayed feeding in a private Brazil ICU M. B. Velasco, D. M. Dalcomune, E. B. Dias, S. L. Fernandes P284 - Can ventilator derived energy expenditure measurements replace indirect calorimetry? T. Oshima, S. Graf, C. Heidegger, L. Genton, V. Karsegard, Y. Dupertuis, C. Pichard P285 - Revisiting the refeeding syndrome: results of a systematic review N. Friedli, Z. Stanga, B. Mueller, P. Schuetz P286 - Compliance with the new protocol for parenteral nutrition in our ICU L. Vandersteen, B. Stessel, S. Evers, A. Van Assche, L. Jamaer, J. Dubois P287 - Nutrition may be another treatment in the intensive care unit where less is more? R. Marinho, H. Castro, J. Moura, J. Valente, P. Martins, P. Casteloes, C. Magalhaes, S. Cabral, M. Santos, B. Oliveira, A. Salgueiro, A. Marinho P288 - Should we provide more protein to critically ill patients? R. Marinho, M. Santos, E. Lafuente, H. Castro, S. Cabral, J. Moura, P. Martins, B. Oliveira, A. Salgueiro, S. Duarte, S. Castro, M. Melo, P. Casteloes, A. Marinho P289 Protein provision in an adult intensive care unit S. Gray P290 - Prevalence and clinical outcomes of vitamin d deficiency in the medical critically ill patients in Songklanagarind hospital K. Maipang, R. Bhurayanontachai P291 - Vitamin d deficiency strongly predicts adverse medical outcome across different medical inpatient populations: results from a prospective study L. G. GrÃ¤del, P. SchÃ¼tz P292 - Omega-3 fatty acids in patients undergoing cardiac surgery: a systematic review and meta-analysis P. Langlois, W. Manzanares P293 - Can 5-hydroxytriptophan prevent post-traumatic stress disorder in critically ill patients? R. Tincu, C. Cobilinschi, D. Tomescu, Z. Ghiorghiu, R. Macovei P294 - Parenteral selenium in the critically ill: an updated systematic review and meta-analysis W. Manzanares, P. Langlois, M. Lemieux, G. Elke, F. Bloos, K. Reinhart, D. Heyland P295 - Probiotics in the critically ill: an updated systematic review and meta-analysis P. Langlois, M. Lemieux, I. Aramendi, D. Heyland, W. Manzanares P296 - Diabetes with hyperglycemic crisis episodes may be associated with higher risk of pancreatic cancer: a population-based cohort study Y. Su P297 - Incidence of hypoglycemia in an intensive care unit depending on insulin protocol R. Marinho, N. Babo, A. Marinho P298 - Severity of the diseases is two-dimensionally correlated to blood glucose, including blood glucose variability, especially in moderately to severely ill patients with glucose intolerance. M. Hoshino, Y. Haraguchi, S. Kajiwara, T. Mitsuhashi, T. Tsubata, M. Aida P299 - A study of glycemic control by subcutaneous glargine injection transition from continuous regular insulin infusion in critically ill patients T. Rattanapraphat, R. Bhurayanontachai, C. Kongkamol, B. Khwannimit P300 - Glycemic control in Portuguese intensive care unit R. Marinho, M. Santos, H. Castro, E. Lafuente, A. Salgueiro, S. Cabral, P. Martins, J. Moura, B. Oliveira, M. Melo, B. Xavier, J. Valente, C. Magalhaes, P. Casteloes, A. Marinho P301 - Impact of hyperglycemia duration on the day of operation on short-term outcome of cardiac surgery patients D. Moisidou, F. Ampatzidou, C. Koutsogiannidis, M. Moschopoulou, G. Drossos P302 - Lactate levels in diabetic ketoacidosis patients at ICU admissions G. Taskin, M. Ã‡akir, AK GÃ¼ler, A. Taskin, N. Ã–cal, S. Ã–zer, L. Yamanel P303 - Intensive care implications of merging heart attack centre units in London J. M. Wong, C. Fitton, S. Anwar, S. Stacey P304 - Special characteristics of in-hospital cardiac arrests M. Aggou, B. Fyntanidou, S. Patsatzakis, E. Oloktsidou, K. Lolakos, E. Papapostolou, V. Grosomanidis P305 - Clinical evaluation of ICU-admitted patients who were resuscitated in the general medicine ward S. Suda, T. Ikeda, S. Ono, T. Ueno, Y. Izutani P306 - Serious game evaluation of a one-hour training basic life support session for secondary school students: new tools for future bystanders S. Gaudry, V. Desailly, P. Pasquier, PB Brun, AT Tesnieres, JD Ricard, D. Dreyfuss, A. Mignon P307 - Public and clinical staff perceptions and knowledge of CPR compared to local and national data J. C White, A. Molokhia, A. Dean, A. Stilwell, G. Friedlaender P308 Dispatcher-assisted telephone cardiopulmonary resuscitation using a French-language compression-ventilation pediatric protocol M. Peters, S. Stipulante, A. Delfosse, AF Donneau, A. Ghuysen P309 Dantrolene versus amiodarone for resuscitation â€" an experimental study C. Feldmann, D. Freitag, W. Dersch, M. Irqsusi, D. Eschbach, T. Steinfeldt, H. Wulf, T. Wiesmann P310 Long term survival and functional neurological outcome in comatose survivors undergoing therapeutic hypothermia N. Kongpolprom, J. Cholkraisuwat P311 Impact of kidney disease on mortality and neurological outcome in out-of-hospital cardiac arrest: a prospective observational study S. Beitland, E. Nakstad, H. StÃ¦r-Jensen, T. DrÃ¦gni, G. Andersen, D. Jacobsen, C. Brunborg, B. Waldum-Grevbo, K. Sunde P312 ICU dependency of patients admitted after primary percutaneous coronary intervention (PPCI) following out of the hospital cardiac arrest K. Hoyland, D. Pandit P313 Prognostic indicators and outcome prediction model for patients with return of spontaneous circulation from cardiopulmonary arrest: comprehensive registry of in-hospital intensive care on OHCA survival (critical) study in Osaka, Japan K. Hayakawa P314 Cerebral oxygen saturation during resuscitation in a porcine model of cardiac arrest E. Oloktsidou, K. Kotzampassi, B. Fyntanidou, S. Patsatzakis, L. Loukipoudi, E. Doumaki, V. Grosomanidis P315 Presumption of cardiopulmonary resuscitation for sustaining cerebral oxidation using regional cerebral saturation of oxygen: observational cohort study (press study) H. Yasuda P316 EEG reactivity in patients after cardiac arrest: a close look at stimuli MM Admiraal, M. Van Assen, MJ Van Putten, M. Tjepkema-Cloostermans, AF Van Rootselaar, J. Horn P317 Prognostic value of neuron-specific enolase after cardiac arrest F. Ragusa, A. Marudi, S. Baroni, A. Gaspari, E. Bertellini P318 Correlation between electroencephalographic findings and serum neuron specific enolase with outcome of post cardiac arrest patients A. Taha, T. Abdullah, S. Abdel Monem P319 Introduction of a targeted temperature management strategy following cardiac arrest in a district general hospital intensive care unit. S. Alcorn, S. McNeill, S. Russell P320 The evolution of cerebral oxygen saturation in post-cardiac arrest patients treated with therapeutic hypothermia W. Eertmans, C. Genbrugge, I. Meex, J. Dens, F. Jans, C. De Deyne P321 Prognostic factors and neurological outcomes of therapeutic hypothermia in comatose survivors from cardiac arrest: 8-year single center experience J. Cholkraisuwat, N. Kongpolprom P322 Adherence to targeted temperature management after out of hospital cardiac arrest B. Avard, R. Burns P323 Implementation of a therapeutic hypothermia protocol for comatose survivors of out-of-hospital cardiac arrest. A. Patarchi, T. Spina P324 Factors associated with ventilator weaning after targeted temperature management for cardiac arrest patients in japan H. Tanaka, N. Otani, S. Ode, S. Ishimatsu P325 Differential activation of c-fos in paraventricular nuclei of the hypothalamus and thalamus of the rat following myocardial infarction J. Cho, J. B. Moon, C. W. Park, T. G. Ohk, M. C. Shin, M. H. Won P326 Monitoring of cTroponin I in patients with acute ischemic stroke - predictor of inhospital mortality S. Dakova, Z. Ramsheva, K. Ramshev P327 Hyperthermic preconditioning severely accelerates neuronal damage in the gerbil ischemic hippocampal dentate gyrus via decreasing sods expressions J. Cho, J. B. Moon, C. W. Park, T. G. Ohk, M. C. Shin P328 Failure in neuroprotection of remote limb ischemic post conditioning in the hippocampus of a gerbil model of transient cerebral ischemia J. Cho, J. B. Moon, C. W. Park, T. G. Ohk, M. C. Shin P329 Brain death and admission diagnosis in neurologic intensive care unit, a correlation? A Marudi, S Baroni, A Gaspari, E Bertellini P330 Brain magnetic resonance imaging findings in patients with septic shock G. Orhun, E. Senturk, P. E. Ozcan, S. Sencer, C. Ulusoy, E. Tuzun, F . Esen P331 Benefits of L-carnitine in valproic acid induced encephalopathy R. Tincu, C. Cobilinschi, D. Tomescu, Z. Ghiorghiu, R. Macovei P332Automatic analysis of EEG reactivity in comatose patients M. Van Assen, M. M. Admiraal, M. J. Van Putten, M. Tjepkema-Cloostermans, A. F. Van Rootselaar, J. Horn P333 Usefulness of common ICU severity scoring systems in predicting outcome after spontaneous intracerebral hemorrhage M. Fallenius, M. B. Skrifvars, M. Reinikainen, S. Bendel, R. Raj P334 Evalution of patients with suspected subarachnoid haemorrhage and negative ct imaging M. Abu-Habsa, C. Hymers, A. Borowska, H. Sivadhas, S. Sahiba, S. Perkins P335 Timing of endovascular and surgical treatment for aneurysmal subarachnoid haemorrhage: early but not so fast. J. Rubio, J. A. Rubio, R. Sierra P336 Red blood cell transfusion in aneurysmal subarachnoid hemorrhage â€" the Sahara cohort study S. English, M. Chasse, A. Turgeon, F. Lauzier, D. Griesdale, A. Garland, D. Fergusson, R. Zarychanski, A. Tinmouth, C. Van Walraven, K. Montroy, J. Ziegler, R. Dupont Chouinard, R. Carignan, A. Dhaliwal, C. Lum, J. Sinclair, G. Pagliarello, L. McIntyre P337 - Aneurysmal subarachnoid hemorrhage and anemia: a canadian multi-centre retrospective cohort study S. English, M. Chasse, A. Turgeon, F. Lauzier, D. Griesdale, A. Garland, D. Fergusson, R. Zarychanski, A. Tinmouth, C. Van Walraven, K. Montroy, J. Ziegler, R. Dupont Chouinard, R. Carignan, A. Dhaliwal, C. Lum, J. Sinclair, G. Pagliarello, L. McIntyre P338 - Does the neutrophil-to-lymphocyte (NLR) ratio predict symptomatic vasospasm or delayed cerebral ischemia (DCI) after aneurysmal subarachnoid haemorrhage (SAH)? T. Groza, N. Moreau, D. Castanares-Zapatero, P. Hantson P339 - ICU-acquired infections in aneurysmal subarachnoid hemorrhage patients: impact on ICU and hospital length of stay M. Carbonara, F. Ortolano, T. Zoerle, S. Magnoni, S. Pifferi, V. Conte, N. Stocchetti P340 - Cerebral metabolic effects of normobaric hyperoxia during the acute phase of aneurysmal subarachnoid hemorrhage L. Carteron, T. Suys, C. Patet, H. Quintard, M. Oddo P341 - Postoperative care for elective craniotomy: where is best done? J. A. Rubio, J. Rubio, R. Sierra P342 - 5-year follow-up of patients after transplantation of organs from donors from neurocritical care V. Spatenkova, E. Pokorna, P. Suchomel P343 - Evaluation of levetiracetam pharmacokinetics after severe traumatic brain injury in neurocritical care patients at a level one trauma center N. Ebert, J. Jancik, H. Rhodes P344 - Model based time series cluster analysis to determine unique patient states in traumatic brain injury T. Bylinski, C. Hawthorne, M. Shaw, I. Piper, J. Kinsella P345 - Brain compartment monitoring capabilities from ICP to BI (bioimpedance) during HS (hypertonic saline) administration. State of art simulation outcome depending on brain swelling type A. K. Kink, I. R. RÃ¤tsep P346 - Transfusion of red blood cells in patients with traumatic brain injury admitted to Canadian trauma health centers: a multicenter cohort study A. Boutin, L. Moore, M. Chasse, R. Zarychanski, F. Lauzier, S. English, L. McIntyre, J. Lacroix, D. Griesdale, P. Lessard-Bonaventure, A. F. Turgeon P347 - Hemoglobin thresholds and red blood cell transfusions in adult patients with moderate or severe traumatic brain injury: a retrospective cohort study A. Boutin, L. Moore, R. Green, P. Lessard-Bonaventure, M. Erdogan, M. Butler, F. Lauzier, M. Chasse, S. English, L. McIntyre, R. Zarychanski, J. Lacroix, D. Griesdale, P. Desjardins, D. A. Fergusson, A. F. Turgeon P348 - Characteristics of patients with gunshot wounds to the head - an observational Brazilian study B. Goncalves, B. Vidal, C. Valdez, A. C. Rodrigues, L. Miguez, G. Moralez P349 - Base excess as predictor for ICU admission and the injury severity in blunt trauma patients T. Hong P350 - Enhancement of usual emergency department care with proadrenomedullin to improve outcome prediction - Results from the multi-national, prospective, observational TRIAGE study A. Kutz, P. Hausfater, D. Amin, T. Struja, S. Haubitz, A. Huber, B. Mueller, P. Schuetz P351 - Developing an innovative emergency medicine point-of-care simulation programme T. Brown, J. Collinson, C. Pritchett, T. Slade P352 - The InSim program: an in situ simulation program for junior trainees in intensive care M. Le Guen, S. Hellings, R. Ramsaran P353 - Impact of excessive and inappropriate troponin testing in the emergency setting how good are we A. Alsheikhly P354 - The development of time tracking monitor at emergency department T. Abe P355 - Role of focussed echocardiography in emergency assessment of syncope L. Kanapeckaite, M. Abu-Habsa, R. Bahl P356 - Insertion of an open-ended 14-gauge catheter through the chest wall causes a significant pneumothorax in a self-ventilating swine model M. Q Russell, K. J. Real, M. Abu-Habsa, R. M. Lyon, N. P. Oveland P357 - Ez-ioÂ® intraosseous access teaching in the workplace using a mobile â€˜tea trolleyâ€™ training method J. Penketh, M. Mcdonald, F. Kelly P358 - Black widow envenomation in Saudi Arabia: a prospective observational case series M. Alfafi, S. Alsolamy, W. Almutairi, B. Alotaibi P359 - Mechanical ventilation in patients with overdose not yet intubated on icu admission A. E. Van den Berg, Y. Schriel, L. Dawson, I. A. Meynaar P360 - Central nervous system depressants poisoning and ventilator associated pneumonia: an underrated risk factor in toxicological intensive care unit H. Talaie P361 - Acute barium intoxication treated with hemodiafiltration D. Silva, S. Fernandes, J. Gouveia, J. Santos Silva P362 - Major trauma presenting to the emergency department. the spectrum of cycling injuries in Ireland J. Foley, A. Kaskovagheorgescu, D. Evoy, J. Cronin, J. Ryan P363 - Burns from French military operations: a 14-year retrospective observational analysis. M. Huck, C. Hoffmann, J. Renner, P. Laitselart, N. Donat, A. Cirodde, J. V. Schaal, Y. Masson, A. Nau, T. Leclerc P364 - A comparison of mortality scores in burns patients on the intensive care unit. O. Howarth, K. Davenport, P. Jeanrenaud, S. Raftery P365 - Clasification of pain and its treatment and an intensive care rehabiliation clinic P. MacTavish, H. Devine, J. McPeake, M. Daniel, J. Kinsella, T. Quasim P366 - Pain management adequacy in critical care areas, the process and the barriers perceived by critical care nurses S. Alrabiee, A. Alrashid, S. Alsolamy P367 - Pain assessment in critically ill adult patients: validation of the Turkish version of the critical-care pain observation tool O. Gundogan, C. Bor, E. AkÃ½n Korhan, K. Demirag, M. Uyar P368 - An audit of pain and sedation assessments in the intensive care unit: recommendations for clinical practice F. Frame, C. Ashton, L. Bergstrom Niska P369 - Impact of pharmaceutical care on treatment of pain and agitation in medical intensive care unit P. Dilokpattanamongkol, T. Suansanae, C. Suthisisang, S. Morakul, C. Karnjanarachata, V. Tangsujaritvijit P370 - Agitation in trauma ICU, prevention and outcome S. Mahmood, H. Al Thani, A. Almenyar P371 Correlation between percentages of ventilated patients developed vap and use of sedative agents in icu patients. A. Vakalos, V. Avramidis P372 - Improving recording of sedation events in the Emergency Department: The implementation of the SIVA International Taskforce adverse event reporting tool for procedural sedation R. Sharvill, J. Penketh P373 - Impact of sedative drug use on the length of mechanical ventilation S. E. Morton, Y. S. Chiew, C. Pretty, J. G. Chase, G. M. Shaw P374 - Co-administration of nitric oxide and sevoflurane using anaconda R. Knafelj, P. Kordis P375 - A retrospective study of the use of Dexmedetomidine in an oncological critical care setting S. Patel, V. Grover P376 - Dexmedetomidine and posttraumatic stress disorder incidence in alcohol withdrawal icu patients I. Kuchyn, K. Bielka P377 - Hemodynamic effects of dexmedetomidine in a porcine model of septic shock Z. Aidoni, V. Grosomanidis, K. Kotzampassi, G. Stavrou, B. Fyntanidou, S. Patsatzakis, C. Skourtis P378 - Ketamine for analgosedation in severe hypoxic respiratory failure S. D. Lee, K. Williams, I. D. Weltes P379 - Madness from the moon? lunar cycle and the incidence of delirium on the intensive care unit S. Berhane, C. Arrowsmith, C. Peters, S. Robert P380 - Impaired dynamic cerebral autoregulation after coronary artery bypass grafting and association with postoperative delirium J. Caldas, R. B. Panerai, T. G. Robinson, L. Camara, G. Ferreira, E. Borg-Seng-Shu, M. De Lima Oliveira, N. C. Mian, L. Santos, R. Nogueira, S. P. Zeferino, M. Jacobsen Teixeira, F. Galas, L. A. Hajjar P381 - Risk factors predicting prolonged intensive care unit length of stay after major elective surgery. P. Killeen, M. McPhail, W. Bernal, J. Maggs, J. Wendon, T. Hughes P382 - Systemic inflammatory response syndrome criteria and hospital mortality prediction in a brazilian cohort of critically ill patients L. U. Taniguchi, E. M. Siqueira, J. M. Vieira Jr, L. C. Azevedo P383 - Evaluating the efficacy of a risk predictor panel in identifying patients at elevated risk of morbidity following emergency admission A. N. Ahmad, M. Abu-Habsa, R. Bahl, E. Helme, S. Hadfield, R. Loveridge P384 - A retrospective comparison of outcomes for elective surgical patients admitted post-operatively to the critical care unit or general ward J. Shak, C. Senver, R. Howard-Griffin P385 - Effect of obesity on mortality in surgical critically ill patients. P. Wacharasint, P. Fuengfoo, N. Sukcharoen, R. Rangsin P386 - The national early warning score (news) reliably improves adverse clinical outcome prediction in community-acquired pneumonia - results from a 6Â year follow-up D. Sbiti-Rohr, P. Schuetz P387 - Clinical usefulness of the charlsonÂ¡Â¯s weighted index of comorbidities _as prognostic factor in patients with prolonged acute mechanical ventilation H. Na, S. Song, S. Lee, E. Jeong, K. Lee P388 - Comparison of mortality prediction scoring systems in patients with cirrhosis admitted to general intensive care unit M. Cooper, K. Milinis, G. Williams, E. McCarron, S. Simants, I. Patanwala, I. D. Welters P389 - Impact of admission source and time of admission on outcome of pediatric intensive care patients: retrospective 15Â years study E. Zoumpelouli, EA Volakli, V. Chrysohoidou, S. Georgiou, K. Charisopoulou, E. Kotzapanagiotou, V. Panagiotidou, K. Manavidou, Z. Stathi, M. Sdougka P390 - Heart rate variability and outcomes prediction in critical illness N. Salahuddin, B. AlGhamdi, Q. Marashly, K. Zaza, M. Sharshir, M. Khurshid, Z. Ali, M. Malgapo, M. Jamil, A. Shafquat, M. Shoukri, M. Hijazi P391 - The incidence and outcome of hyperlactatemia in the post anaesthesia care unit T. Abe, S. Uchino, M. Takinami P392 - Correlation between arterial blood gas disturbances and arterial lactate levels during hospitalization and outcome in critically septic patients N. R. Rangel Neto, S. Oliveira, F. Q. Reis, F. A. Rocha P393 - External validation of saps 3 and mpm iii scores in 48, 816 patients from 72 brazilian icus G. Moralez, K. Ebecken, L. S. Rabello, M. F. Lima, R. Hatum, F. V. De Marco, A. Alves, J. E. Pinto, M. Godoy, P. E. Brasil, F. A. Bozza, J. I. Salluh, M. Soares P394 - The frailty penalty: pre-admission functional status confounds mortality prediction models in critically ill patients J. Krinsley, G. Kang P395 - â€˜sooner rather than laterâ€: how delayed discharge from critical care leads to increased out of hours discharges and subsequent increase in in-hospital mortality. J. Perry, H. Hines P396 - Identifying poor outcome patient groups in a resource-constrained critical care unit K. M. Wilkinson, C. Tordoff, B. Sloan, M. C. Bellamy P397 - Effects of icu weekend admission and discharge on mortality. E. Moreira, F. Verga, M. Barbato, G. Burghi P398 - Organizational factors, outcomes and resource use in 9, 946 cancer patients admitted to 70 ICUs M Soares, U. V. Silva, L. C. Azevedo, A. P. Torelly, J. M. Kahn, D. C. Angus, M. F. Knibel, P. E. Brasil, F. A. Bozza, J. I. Salluh P399 - Evaluation of oncological critically ill patients, severity score and outcome compared to not oncological in a particular hospital cti. M. B. Velasco, D. M. Dalcomune P400 - Outcomes of patients admitted to a large uk critical care department with palliative oncological diagnoses R. Marshall, T. Gilpin, A. Tridente, A. Raithatha P401 - Predictors of mortality in febrile neutropenic patients with haematological malignancies admitted to an intensive care unit of a cancer center D. Mota, B. Loureiro, J. Dias, O. Afonso, F. Coelho, A. Martins, F. Faria P402 - Patients with hematologic malignancies requiring invasive mechanical ventilation: characteristics and predictors of mortality H. Al-Dorzi, H. Al Orainni, F. AlEid, H. Tlaygeh, A. Itani, A. Hejazi, Y. Arabi P403 - Patient-important outcomes in randomized controlled trials in critically ill patients: a systematic review S. Gaudry, J. Messika, J. D. Ricard, S. Guillo, B. Pasquet, E. Dubief, D. Dreyfuss, F. Tubach P404 - Alopecia in survivors of critical illness: a qualitative study C . Battle, K. James, P. Temblett P405 - The impact of mental health on icu admission L. Davies, C. Battle, C. Lynch P406 - Cognitive impairment 5Â years after ICU discharge S. Pereira, S. Cavaco, J. Fernandes, I. Moreira, E. Almeida, F. Seabra Pereira, M. Malheiro, F. Cardoso, I. AragÃ£o, T. Cardoso P407 - Apache ii versus apache iv for octagenerians in medical icu M. Fister, R. Knafelj P408 - Outcomes of octagenarians in an indian icu P. Muraray Govind, N. Brahmananda Reddy, R. Pratheema, E. D. Arul, J. Devachandran P409 - Mortality and outcomes in elderly patients 80Â years of age or older admitted to the icu M. B. Velasco, D. M. Dalcomune P410 - Octagenerians in medical icu - adding days to life or life to days? R. Knafelj, M. Fister P411 - The very elderly admitted to intensive care unit: outcomes and economic evaluation N. Chin-Yee, G. Dâ€™Egidio, K. Thavorn, D. Heyland, K. Kyeremanteng P412 - The very elderly in intensive care: relationship between acuity of illness and long-term mortality A. G. Murchison, K. Swalwell, J. Mandeville, D. Stott P413 - Acquired weakness in an oncological intensive care unit I. Guerreiro P414 - Musculoskeletal problems in intensive care unit (ICU) patients post-discharge H. Devine, P. MacTavish, J. McPeake, T. Quasim, J. Kinsella, M. Daniel P415 - Premorbid obesity, but not nutrition, prevents critical illness-induced muscle wasting and weakness C. Goossens M. B. Marques, S. Derde, S. Vander Perre, T. Dufour, S. E. Thiessen, F. GÃ¼iza, T. Janssens, G. Hermans, I. Vanhorebeek, K. De Bock, G. Van den Berghe, L. Langouche P416 - Physical outcome measures for critical care patients following intensive care unit (icu) discharge H. Devine, P. MacTavish, T. Quasim, J. Kinsella, M. Daniel, J. McPeake P417 - Improving active mobilisation in a general intensive care unit B. Miles, S. Madden, H. Devine P418 - Mobilization in patients on vasoactive drugs use â€" a pilot study. M. Weiler, P. Marques, C. Rodrigues, M. Boeira, K. Brenner, C. LeÃ£es, A. Machado, R. Townsend, J. Andrade P419 - Pharmacy intervention at an intensive care rehabilitation clinic P. MacTavish, J. McPeake, H. Devine, J. Kinsella, M. Daniel, R. Kishore, C. Fenlon, T. Quasim P420 - Interactive gaming is feasible and potentially increases icu patientsâ€™ motivation to be engaged in rehabilitation programs T. Fiks, A. Ruijter, M. Te Raa, P. Spronk P421 - Simulation-based design of a robust stopping rule to ensure patient safety Y. S. Chiew, P. Docherty, J. Dickson, E. Moltchanova, C. Scarrot, C. Pretty, G. M. Shaw, J. G. Chase P422 - Are daily blood tests on the intensive care unit necessary? T. Hall, W. C. Ngu, J. M. Jack, P. Morgan P423 - Measuring urine output in ward patients: is it helpful? B. Avard, A. Pavli, X. Gee P424 - The incidence of pressure ulcers in an adult mixed intensive care unit in turkey C . Bor, E. Akin Korhan, K. Demirag, M. Uyar P425 - Intensivist/patient ratios in closed ICUs in Alexandria, Egypt; an overview M. Shirazy, A. Fayed P426 - Eicu (electronic intensive care unit): impact on ALOS (average length of stay) in a developing country like India S. Gupta, A. Kaushal, S. Dewan, A. Varma P427 - Predicting deterioration in general ward using early deterioration indicator E. Ghosh, L. Yang, L. Eshelman, B. Lord, E. Carlson P428 - High impact enhanced critical care outreach - the imobile service: making a difference E. Helme, R. Broderick, S. Hadfield, R. Loveridge P429 - Impact of bed availability and cognitive load on intensive care unit (ICU) bed allocation: a vignette-based trial J. Ramos, D. Forte P430 - Characteristics of critically ill patients admitted through the emergency department F. Yang, P. Hou P431 - Admission to critical care: the quantification of functional reserve J. Dudziak, J. Feeney, K. Wilkinson, K. Bauchmuller, K. Shuker, M. Faulds, A. Raithatha, D. Bryden, L. England, N. Bolton, A. Tridente P432 - Admission to critical care: the importance of frailty K. Bauchmuller, K Shuker, A Tridente, M Faulds, A Matheson, J. Gaynor, D Bryden, S South Yorkshire Hospitals Research Collaboration P433 - Development of an instrument to aid triage decisions for intensive care unit admission J. Ramos, B. Peroni, R. Daglius-Dias, L. Miranda, C. Cohen, C. Carvalho, I . Velasco, D. Forte P434 - Using selective serotonin re-uptake inhibitors and serotonin-norepinephrine re-uptake inhibitors in critical care: a systematic review of the evidence for benefit or harm J. M. Kelly, A. Neill, G. Rubenfeld, N. Masson, A. Min P435 - Measuring adaptive coping of hospitalized patients with a severe medical condition:the sickness insight in coping questionnaire (sicq) E. Boezeman, J. Hofhuis, A. Hovingh, R. De Vries, P. Spronk P436 - Results of a national survey regarding intensive care medicine training G. Cabral-Campello, I. AragÃ£o, T. Cardoso P437 - Work engagement among healthcare professionals in the intensive care unit M. Van Mol, M. Nijkamp, E . Kompanje P438 - Empowering the intensive care practitioners. is it a burnout ameliorating intervention? P. Ostrowski, A. Omar P439 - Icu patients suffer from circadian rhythm desynchronisation K. Kiss, B. KÃ¶ves, V. Csernus, Z. MolnÃ¡r P440 - Noise reduction in the ICU: feasible ? Y. Hoydonckx, S. Vanwing, B. Stessel, A. Van Assche, L. Jamaer, J. Dubois P441 - Accidental removal of invasive devices in the critical patient into the bed-washing. does the presence of professional nurse modify his incidence? V. Medo, R. Galvez, J. P. Miranda P442 - Deprivation of liberty safeguards (dols): audit of compliance in a of a 16-bed specialist cancer critical care unit. C. Stone, T. Wigmore P443 - Use of a modified cristal score to predict futility of critical care in the elderly Y. Arunan, A. Wheeler, K. Bauchmuller, D. Bryden P444 - Improvement of Referral Rate to Palliative Care for Patients with Poor Prognosis in Neurosurgical Intensive Care Unit Y. Wong, C. Poi, C. Gu P445 - Factors associated with limitation of life supporting care (lsc) in a medico-surgical intermediate care unit, and outcome of patients with lsc limitation: a monocentric, six-month study. P. Molmy, N. Van Grunderbeeck, O. Nigeon, M. Lemyze, D. Thevenin, J. Mallat P446 - Palliative care consultation and intensive care unit admission request: a cohort study J. Ramos, M. Correa, R. T. Carvalho, D. Forte P447 - Nursing and medicine together in postsurgical intensive care unit: situations of prognostic conflict at the end of life. our critical care nurses suffer with our medical activism? A. Fernandez, C. McBride P448 - End of life who may decide E. Koonthalloor, C. Walsh P449 - Correctly diagnosing death A. Webber, M. Ashe, K. Smith, P. Jeanrenaud P450 - Skin procurement performed by intensive care physicians: yes, we can. A. Marudi, S. Baroni, F. Ragusa, E. Bertellini P451 - Death analysis in pediatric intensive care patients E. A. Volakli, E. Chochliourou, M. Dimitriadou, A. Violaki, P. Mantzafleri, E. Samkinidou, O. Vrani, A. Arbouti, T. Varsami, M. Sdougka P452 - The potential impact of euthanasia on organ donation: analysis of data from belgium J. A. Bollen, T. C. Van Smaalen, W. C. De Jongh, M. M. Ten Hoopen, D. Ysebaert, L. W. Van Heurn, W. N. Van Mook P453 - Communication within an intensive care setting K. Sim, A. Fuller P454 - Development and implementation of a longitudinal communication curriculum for critical care medicine fellows A. Roze des Ordons, P. Couillard, C. Doig P455 - Staff-family conflict in a multi-ethnic intensive care unit R. V. Van Keer, R. D. Deschepper, A. F. Francke, L. H. Huyghens, J. B. Bilsen P456 - Does the source of admission to critical care affect family satisfaction? B. Nyamaizi, C. Dalrymple, A. Molokhia, A. Dobru P457 - A simple alternative to the family satisfaction survey (fs-icu) E. Marrinan, A. Ankuli, A. Molokhia P458 - A study to explore the experiences of patient and family volunteers in a critical care environment: a phenomenological analysis J. McPeake, R. Struthers, R. Crawford, H. Devine, P. Mactavish, T. Quasim P459 - Prevalence and risk factors of anxiety and depression in relatives of burn patients. P. Morelli, M. Degiovanangelo, F. Lemos, V. MArtinez, F. Verga, J. Cabrera, G. Burghi P460 - Guidance of visiting children at an adult intensive care unit (icu) A. Rutten, S. Van Ieperen, S. De Geer, M. Van Vugt, E. Der Kinderen P461 - Visiting policies in Italian pediatric ICUs: an update A. Giannini, G Miccinesi, T Marchesi, E Prandi